Multiplicity dependence of (multi-)strange hadron production in proton-proton collisions at √s=13 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Knichel, Michael Linus; Köhler, Markus Konrad; Leardini, Lucia; et al. (The European physical journal. C, Particles and fields, 2020)
The production rates and the transverse momentum distribution of strange hadrons at mid-rapidity (vertical bar y vertical bar < 0.5) are measured in proton-proton collisions at root s = 13 TeV as a function of the charged particle multiplicity, using the ALICE detector at the LHC. The production rates of K-S(0), Lambda, Xi, and Omega increase with the multiplicity faster than what is reported for inclusive charged particles. The increase is found to be more pronounced for hadrons with a larger strangeness content. Possible auto-correlations between the charged particles and the strange hadrons are evaluated by measuring the event-activity with charged particle multiplicity estimators covering different pseudorapidity regions. When comparing to lower energy results, the yields of strange hadrons are found to depend only on the mid-rapidity charged particle multiplicity. Several features of the data are reproduced qualitatively by general purpose QCD Monte Carlo models that take into account the effect of densely-packed QCD strings in high multiplicity collisions. However, none of the tested models reproduce the data quantitatively. This work corroborates and extends the ALICE findings on strangeness production in proton-proton collisions at 7 TeV.